2019
DOI: 10.1021/acsomega.9b02168
|View full text |Cite
|
Sign up to set email alerts
|

CLG from Hemp Seed Inhibits LPS-Stimulated Neuroinflammation in BV2 Microglia by Regulating NF-κB and Nrf-2 Pathways

Abstract: The healthy benefits of hemp (Cannabis sativa L.) seed have often been attributed to its oils and proteins. Recent studies reveal that hemp seed phenylpropionamides could also show various bioactivities. Continuation of our study on hemp seed provided a phenylpropionamide, coumaroylaminobutanol glucopyranoside (CLG). This work investigated the neuroprotective effect of CLG and its underlying mechanism using lipopolysaccharide-induced BV2 microglia. Our study demonstrated that CLG increased adenosine monophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…To understand the molecular mechanism underlying the neuroprotective action of the most bioactive hempseed phenylpropionamides, various studies were performed by different authors. More specifically, to date, the investigated compounds were CLG [ 108 ], grossamide [ 109 ], and cannabisin F [ 110 ]. In all cases, BV2 microglia cells were pre-treated with 5, 10, or 15 µM of each tested compound 1 h before the addition of 100 ng/mL of LPS for 24 h. After 24 h of LPS exposure, it has been shown that all three lignanamides were able to decrease the release of the inflammatory cytokines IL-1β, IL-6, and TNF-α in a dependent-manner by the inactivation at different level of the NF-κB inflammatory pathway.…”
Section: C Sativa L Seedmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the molecular mechanism underlying the neuroprotective action of the most bioactive hempseed phenylpropionamides, various studies were performed by different authors. More specifically, to date, the investigated compounds were CLG [ 108 ], grossamide [ 109 ], and cannabisin F [ 110 ]. In all cases, BV2 microglia cells were pre-treated with 5, 10, or 15 µM of each tested compound 1 h before the addition of 100 ng/mL of LPS for 24 h. After 24 h of LPS exposure, it has been shown that all three lignanamides were able to decrease the release of the inflammatory cytokines IL-1β, IL-6, and TNF-α in a dependent-manner by the inactivation at different level of the NF-κB inflammatory pathway.…”
Section: C Sativa L Seedmentioning
confidence: 99%
“…Normally, this protein is located in the cytoplasm, but in response to oxidative stimuli, Nrf2 transferred to the nucleus and activated downstream genes involved in the antioxidant defence. Although LPS stimulation leads to an increased production of ROS by microglia-stimulated cells, it has been demonstrated that the pre-treatment with CLG or cannabisin F upregulated the Nfr-2 pathway, thus exerting a beneficial antioxidant effect [ 108 , 110 ]. In addition, it has also shown that cannabisin F was able to enhance its inhibitory action on the NF-κB transcription factor even by inhibiting the downregulation of the silent information regulator transcript-1 (SIRT1) induced by LPS.…”
Section: C Sativa L Seedmentioning
confidence: 99%
“…CLG reduces cellular reactive oxygen species assembly and stimulates the nuclear factor erythroid 2-related factor 2 (Nrf-2) signaling pathway. AMPK is also involved in the anti-inflammatory effect of CLG [18]. However, in a study on a cellular model of Parkinson's disease, caffeoyltyramide (hemp seed extract) could not affect cell death induced by rotenone but could protect against H2O2 induced cell death [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hemp seed also has anti-microbial, anti-inflammatory, and anti-lipogenic effects [16] due to a perfectly balanced content of omega three and omega six polyunsaturated fatty acids [17]. Hemp seed also contains a phenylpropionamide, called coumaroyl-amino butanol glucopyranoside (CLG), providing some neuroprotective effects that will be discussed in this article [18]. Recently, some studies have indicated the efficacy of consuming herbal treatments to improve health in MS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation